Preparation method and application of modified carbon material loaded with iron
By constructing an electro-Fenton process using a modified carbon material cathode loaded with iron, H2O2 is generated in situ and ·OH is catalyzed, solving the problems of iron loss and narrow pH range in the traditional Fenton process, and achieving efficient and stable removal of organic pollutants.
Patent Information
- Application Number
- CN202311154633.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-08
- Publication Date
- 2025-11-11
- Estimated Expiration
- 2043-09-08
AI Technical Summary
The traditional Fenton process requires the addition of Fe2+ solution and liquid H2O2, which leads to iron loss, H2O2 consumption and safety risks, and has a narrow pH range. The existing electro-Fenton process requires the addition of ferrous salt, resulting in consumption and difficulties in post-processing.
Using iron-loaded modified carbon material as the cathode, H2O2 is generated in situ from O2 in water, avoiding the addition of liquid H2O2 and ferrous salts. The iron-loaded material catalyzes the formation of ·OH from H2O2, thus broadening the applicable pH range to 3~9.
It increases H2O2 production, avoids the consumption of external reagents and difficulties in post-treatment, and achieves efficient removal of organic pollutants in water over a wide pH range. The cathode maintains stability during repeated use.
Smart Images

Figure CN117049663B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the preparation of an iron-loaded modified carbon material cathode and the electro-Fenton method constructed thereon for the removal of organic pollutants in water, belonging to the field of water pollution control. Background Technology
[0002] Organic pollutants in water bodies are a major factor leading to water quality deterioration. Organic wastewater is typically treated using biological methods; however, industrial wastewater, such as from pharmaceutical, coking, and dye industries, contains large amounts of recalcitrant organic matter, making biological methods difficult to achieve ideal treatment results. Advanced oxidation processes can effectively degrade organic matter in water, with the Fenton oxidation process being one of the most widely used methods. Traditional Fenton oxidation utilizes Fe under acidic conditions (pH 2-5). 2+ The catalytic reaction of H₂O₂ generates hydroxyl radicals (·OH), which are then used to degrade and remove organic matter from water due to their strong oxidizing properties. However, the traditional Fenton process requires the addition of Fe. 2+ The reaction of H2O2 in solution and liquid can easily cause the loss of iron and the consumption of a large amount of H2O2. At the same time, the formation of a large amount of iron sludge after the reaction increases the burden of subsequent treatment. Moreover, liquid H2O2 is an explosive hazardous chemical, and its unstable chemical properties bring risks to its storage, transportation and use.
[0003] In the electro-Fenton process, H2O2 is generated at the cathode; therefore, the cathode's performance determines the H2O2 yield, current efficiency, and energy consumption. Carbon materials are widely used as cathode materials for H2O2 production due to their high hydrogen evolution conductivity, non-toxicity, low cost, high catalytic activity, and high stability. Among them, activated carbon fibers, with their three-dimensional porous structure, large specific active surface area, high conductivity, excellent mechanical integrity, and good adsorption capacity, are very suitable as cathode materials. Summary of the Invention
[0004] The present invention aims to provide a method for preparing an iron-loaded modified carbon material cathode and its application in the electro-Fenton method for removing organic pollutants in water. This method not only overcomes the shortcomings of traditional Fenton and existing electro-Fenton systems, such as narrow applicable pH range and the need for the addition of liquid H2O2 and ferrous salt, but also ensures that the iron-loaded modified carbon material cathode can maintain high removal efficiency and stability even after repeated use.
[0005] In the electro-Fenton system employed in this invention, H2O2 can be generated in situ by reducing O2 in water at the cathode, thus overcoming the hidden dangers associated with the addition of liquid H2O2 in traditional Fenton methods. Using an iron-loaded cathode, the iron catalyzes the continuous generation of free radicals such as ·OH from H2O2, enabling the efficient degradation of organic pollutants in water. Simultaneously, the iron-loaded cathode avoids the losses associated with the addition of ferrous salts and the hassle of subsequent iron sludge disposal. Furthermore, modifying activated carbon fibers with iron-loaded carbon nanotubes not only significantly increases H2O2 production, but also eliminates the need for ferrous salts in the electro-Fenton method using iron-modified carbon cathodes, and, more importantly, broadens the applicable pH range.
[0006] To achieve the above objectives, the technical solution of the present invention is as follows:
[0007] A method for preparing an iron-loaded modified carbon material includes the following steps:
[0008] 1) Take 180-200 mesh carbon nanotube powder, immerse it in concentrated sulfuric acid, dry it, rinse it with deionized water until neutral, sonicate it for 20-30 minutes, filter it and freeze dry it to obtain modified carbon nanotubes with good dispersibility.
[0009] 2) Dissolve iron salt in anhydrous ethanol, add the modified carbon nanotubes obtained in step 1), sonicate for 100-200 min, disperse iron on the carbon nanotubes, and dry to obtain iron-loaded modified carbon nanotubes.
[0010] 3) Grind the iron-loaded modified carbon nanotubes obtained in step 2) into powder, mix them evenly with polytetrafluoroethylene concentrate, dissolve them in isopropanol, stir and add deionized water, coat the resulting mixture on the surface of activated carbon fiber, ultrasonically treat it, and then dry and calcine it to obtain the iron-loaded modified carbon material used as the cathode.
[0011] The carbon nanotube powder in step 1) has a particle size of less than 180 mesh.
[0012] In step 1), the concentrated sulfuric acid is an aqueous solution of sulfuric acid with a weight percentage of 70-90 wt%.
[0013] In step 1), the drying temperature is 140±5℃ and the time is 12~15h.
[0014] In step 1), the freeze-drying temperature is no greater than -50℃ and the vacuum degree is less than 15Pa.
[0015] In step 2), the iron salt is one of ferric chloride FeCl3, ferric sulfate Fe2(SO4)3, or ferric nitrate Fe(NO3)3.
[0016] In step 2), the amount of anhydrous ethanol added is 30~60 mL / mmol Fe.
[0017] In step 2), the drying temperature is 140±5℃ and the time is 9~12h.
[0018] In step 2), the modified carbon nanotubes loaded with iron have an iron mass percentage of 9% to 20%.
[0019] In step 3), the modified carbon nanotubes loaded with iron are ground into powder with a particle size of less than 180 mesh.
[0020] The polytetrafluoroethylene concentrate in step 3) has a weight ratio of 60 wt%.
[0021] In step 3), 1g of iron-loaded modified carbon nanotubes are added to 2-5mL of polytetrafluoroethylene concentrate and dissolved in 4-10mL of analytical grade isopropanol and mixed thoroughly. Then, 150-200mL of deionized water is added and stirred until homogeneous. The mixture is then coated onto a surface with an area of 450-600cm². 2 The surface of activated carbon fibers.
[0022] The drying temperature in step 3) is 80~100℃, and the drying time is 12~24h.
[0023] The calcination temperature in step 3) is 350~400℃, and the calcination is carried out in a muffle furnace for 2~3 hours.
[0024] This invention provides an application of iron-loaded modified carbon material as a cathode in the electro-Fenton process for treating organic pollutants. The cathode of the electro-Fenton process is made by bonding iron-loaded modified carbon material to a graphite plate; the anode can be selected from ruthenium-iridium-titanium electrodes, titanium electrodes, and platinum electrodes.
[0025] The pH range applicable to the electro-Fenton method is 3 to 9.
[0026] The aeration device in the electro-Fenton method can be an air pump with an aeration rate of 0.5~1.5L / min.
[0027] The current density used in the electric Fenton method application is 15~90 mA / cm². 2 .
[0028] The electro-Fenton method is used to remove organic pollutants from water.
[0029] The organic pollutants mentioned include antibiotics, dyes, phenolic organic pollutants, and organic pollutants in domestic sewage and industrial wastewater.
[0030] The cathode made of the above-mentioned iron-loaded modified carbon material can be reused multiple times after being rinsed with deionized water 2-3 times.
[0031] The beneficial effects of this invention are as follows:
[0032] (1) A cathode made of iron-loaded modified carbon material in this invention is prepared by coating iron-loaded modified carbon nanotubes on the surface of activated carbon fibers with a large specific surface area. The electro-Fenton system constructed by this cathode significantly increases the amount of H2O2 generated in situ by the cathode.
[0033] (2) The electro-Fenton system constructed by using iron-loaded modified carbon material as cathode in this invention does not require the addition of ferrous salt, thus avoiding reagent consumption and the trouble of disposing of iron sludge later.
[0034] (3) The electro-Fenton system constructed by using iron-loaded modified carbon material as cathode in this invention can efficiently remove organic matter in the pH range of 3 to 9, and the cathode is stable in repeated use. Attached Figure Description
[0035] Figure 1 This is a schematic diagram of the composition of an electro-Fenton system.
[0036] Figure 2 This is a scanning electron microscope image of the modified carbon nanotubes in Example 1.
[0037] Figure 3 This is a scanning electron microscope image of the modified carbon nanotubes loaded with iron in Example 1.
[0038] Figure 4 The image shows the X-ray diffraction pattern of the iron-loaded modified carbon nanotubes obtained in Example 1.
[0039] Figure 5 The results of the removal of levofloxacin by electro-Fenton method using the iron-loaded modified carbon material obtained in Example 1 as the cathode at different pH values are shown.
[0040] Figure 6 The results of the removal of levofloxacin by electro-Fenton method using the modified carbon material with iron load obtained in Example 2 as the cathode at different current densities are shown.
[0041] Figure 7 The result is the removal of levofloxacin by repeatedly using the modified carbon material with iron load obtained in Example 3 as the cathode in the electro-Fenton method.
[0042] Figure 8 The results of the removal of methyl orange by electro-Fenton method using the iron-loaded modified carbon material obtained in Example 4 as the cathode at different pH values are shown.
[0043] Figure 9 The results of removing COD from secondary sedimentation tank wastewater at pH 7 using the modified carbon material with iron loading obtained in Example 5 as the cathode via the electro-Fenton method. Detailed Implementation
[0044] The present invention will be further illustrated by the following embodiments, but is not limited to the following embodiments. Example 1
[0045] The preparation of iron-loaded modified carbon cathodes and the electro-Fenton method constructed therefor for the removal of levofloxacin (LFV) from water at different pH conditions are as follows:
[0046] (1) Preparation of modified carbon nanotube solid: 200 mg of carbon nanotube powder was placed in 70 wt% concentrated sulfuric acid, stirred, dried at 140 °C for 14 h, rinsed with deionized water until neutral, then ultrasonically treated in deionized water for 20 min, and then freeze-dried for 24 h to obtain modified carbon nanotube material.
[0047] (2) Preparation of iron-loaded modified carbon nanotube solid: Take 0.1g FeCl3·5H2O and put it into 20mL of anhydrous ethanol. Disperse 0.2g of modified carbon nanotubes into the solution and sonicate for 2h to make the solution into a paste. Then dry at 140℃ for 12h to obtain iron-loaded modified carbon nanotube solid.
[0048] Figure 2 These are scanning electron micrographs of modified carbon nanotubes; Figure 3 This is a scanning electron microscope image of the modified carbon nanotubes after iron loading. As can be seen from the image, the surface of the modified carbon nanotubes before loading is relatively smooth and they are in the form of bundles with a diameter of about 10~50nm; the surface of the modified carbon nanotubes after iron loading is uneven, the bundles of nanotubes become thicker, and the morphology of the outer surface changes significantly.
[0049] The X-ray diffraction pattern of the prepared iron-loaded modified carbon nanotubes (CNTs) is shown in the figure. Figure 4 As shown, the appearance of diffraction peaks for carbon nanotubes (CNTs) and Fe2O3 proves that iron was successfully loaded onto the modified carbon nanotubes.
[0050] (3) Preparation of iron-loaded modified carbon material cathode: The above-mentioned iron-loaded modified carbon nanotubes were placed in a mixed solution containing 1 mL of 60% wt polytetrafluoroethylene and 2 mL of analytical grade isopropanol. Then, 30 mL of pure water was added to the mixed solution. The mixed solution was evenly coated on 10 cm * 10 cm activated carbon fibers and ultrasonically treated for 15 min. Then, the carbon fiber cloth was turned over and ultrasonically treated for another 15 min. This process was repeated three times to ensure that the carbon material was fully attached to the activated carbon fibers. Then, the carbon nanotubes were dried at 90 °C for 24 h and then calcined in a muffle furnace at 360 °C for 2 h. After cooling, the iron-loaded modified carbon material was attached to a graphite plate to serve as a cathode.
[0051] (4) Electro-Fenton reaction conditions: The apparatus composition of the electro-Fenton system is as follows Figure 1As shown, the cathode is a modified carbon material cathode loaded with iron, and the anode is a ruthenium-iridium-titanium anode with a plate spacing of 50 mm. Under electric stirring, air is pumped into the solution using an air pump at an aeration rate of 1.2 L / min; the current density is 30 mA / cm². 2 The solution contained 50 mg / L levofloxacin and 50 mM Na₂SO₄. After adjusting the pH and reacting for 240 min, the levofloxacin content was measured, and its degradation rate was calculated. Figure 5 As shown, the degradation rate of levofloxacin is 93%–96% between pH 3 and 9. Example 2
[0052] The preparation of iron-loaded modified carbon cathodes and the application of their electro-Fenton method for removing levofloxacin (LFV) from water under different current densities are as follows:
[0053] (1) Preparation of modified carbon nanotube solid: 200 mg of carbon nanotube powder was placed in 80 wt% concentrated sulfuric acid, stirred, dried at 140 °C for 14 h, rinsed with deionized water until neutral, then ultrasonically treated in deionized water for 20 min, and then freeze-dried for 24 h to obtain modified carbon nanotube material.
[0054] (2) Preparation of iron-loaded modified carbon nanotube solid: Take 0.15g FeCl3·5H2O and put it into 20mL of anhydrous ethanol. Disperse 0.3g of modified carbon nanotubes into the solution and sonicate for 2h to make the solution into a paste. Then dry at 140℃ for 12h to obtain iron-loaded modified carbon nanotube solid.
[0055] (3) Preparation of iron-loaded modified carbon material cathode: The above-mentioned iron-loaded modified carbon nanotubes were placed in a mixed solution containing 1 mL of 60%wt polytetrafluoroethylene and 2 mL of analytical grade isopropanol. Then, 30 mL of pure water was added to the mixed solution. The mixed solution was evenly coated on 10 cm * 10 cm activated carbon fibers and ultrasonically treated for 15 min. Then, the carbon fiber cloth was turned over and ultrasonically treated for another 15 min. This process was repeated three times to ensure that the carbon material was fully attached to the activated carbon fibers. Then, the carbon nanotubes were dried at 100 °C for 24 h and then calcined in a muffle furnace at 360 °C for 2 h. After cooling, the iron-loaded modified carbon material was attached to a graphite plate to serve as a cathode.
[0056] (4) Electro-Fenton reaction conditions: The apparatus composition of the electro-Fenton system is as follows Figure 1As shown, the cathode was a modified carbon material cathode loaded with iron, and the anode was a ruthenium-iridium-titanium anode with a plate spacing of 50 mm. Under electric stirring, air was pumped into the solution using an air pump at an aeration rate of 1.2 L / min. The solution contained 50 mg / L levofloxacin, 50 mM Na₂SO₄, and pH 3. After adjusting the current density and reacting for 240 min, the levofloxacin content in the solution was measured, and its degradation rate was calculated. Figure 6 As shown. Current density range 15~90 mA / cm². 2 The degradation rate of levofloxacin is 90%~100%. Example 3
[0057] The preparation of iron-loaded modified carbon cathodes and their repeated use to construct an electro-Fenton method for the removal of levofloxacin (LFV) from water are as follows:
[0058] (1) Preparation of modified carbon nanotube solid: 200 mg of carbon nanotube powder was placed in 70 wt% concentrated sulfuric acid, stirred, dried at 140 °C for 12 h, rinsed with deionized water until neutral, then ultrasonically treated in deionized water for 20 min, and then freeze-dried for 24 h to obtain modified carbon nanotube material.
[0059] (2) Preparation of iron-loaded modified carbon nanotube solid: Take 0.2g FeCl3·5H2O and put it into 20mL of anhydrous ethanol. Disperse 0.2g of modified carbon nanotubes into the solution and sonicate for 2h to make the solution into a paste. Then dry at 140℃ for 10h to obtain iron-loaded modified carbon nanotube solid.
[0060] (3) Preparation of iron-loaded modified carbon material cathode: The above-mentioned iron-loaded modified carbon nanotubes were placed in a mixed solution containing 1 mL of 60%wt polytetrafluoroethylene and 2 mL of analytical grade isopropanol. Then, 30 mL of pure water was added to the mixed solution. The mixed solution was evenly coated on 10 cm * 10 cm activated carbon fibers and ultrasonically treated for 15 min. Then, the carbon fiber cloth was turned over and ultrasonically treated for another 15 min. This process was repeated three times to ensure that the carbon material was fully attached to the activated carbon fibers. Then, the carbon nanotubes were dried at 100 °C for 24 h and then calcined in a muffle furnace at 360 °C for 2 h. After cooling, the iron-loaded modified carbon material was attached to a graphite plate to serve as a cathode.
[0061] (4) Electro-Fenton reaction conditions: The apparatus composition of the electro-Fenton system is as follows Figure 1 As shown, the cathode is a modified carbon material cathode loaded with iron, and the anode is a ruthenium-iridium-titanium anode with a plate spacing of 50 mm. Air is pumped into the solution using an air pump under electric stirring at an aeration rate of 1.2 L / min. The solution contains 50 mg / L levofloxacin, 50 mM Na₂SO₄, pH 3, and a current density of 30 mA / cm². 2After a reaction of 240 min, the levofloxacin content in the solution was measured, and its degradation rate was calculated. The used cathode was removed, rinsed three times with deionized water, inserted into the apparatus, and the previous experiment was repeated. The results are as follows: Figure 7 As shown.
[0062] After being used repeatedly for 6 cycles, the degradation rate of levofloxacin decreased from 94.3% in the first use to 89.0% in the sixth use. Example 4
[0063] The preparation of iron-loaded modified carbon cathodes and the electro-Fenton method constructed thereon for removing methyl orange dye from water at pH 3 and pH 7 are as follows:
[0064] (1) Preparation of modified carbon nanotube solid: 200 mg of carbon nanotube powder was placed in 90 wt% concentrated sulfuric acid, stirred, dried at 140 °C for 14 h, rinsed with deionized water until neutral, then ultrasonically treated in deionized water for 20 min, and then freeze-dried for 24 h to obtain modified carbon nanotube material.
[0065] (2) Preparation of iron-loaded modified carbon nanotube solid: Take 0.1g FeCl3·5H2O and put it into 20mL of anhydrous ethanol. Disperse 0.2g of modified carbon nanotubes into the solution and sonicate for 2h to make the solution into a paste. Then dry at 140℃ for 12h to obtain iron-loaded modified carbon nanotube solid.
[0066] (3) Preparation of iron-loaded modified carbon material cathode: The above-mentioned iron-loaded modified carbon nanotubes were placed in a mixed solution containing 1 mL of 60%wt polytetrafluoroethylene and 2 mL of analytical grade isopropanol. Then, 30 mL of pure water was added to the mixed solution. The mixed solution was evenly coated on 10 cm * 10 cm activated carbon fibers and ultrasonically treated for 15 min. Then, the carbon fiber cloth was turned over and ultrasonically treated for another 15 min. This process was repeated three times to ensure that the carbon material was fully attached to the activated carbon fibers. Then, the carbon nanotubes were dried at 100 °C for 24 h and then calcined in a muffle furnace at 360 °C for 2 h. After cooling, the iron-loaded modified carbon material was attached to a graphite plate to serve as a cathode.
[0067] (4) Electro-Fenton reaction conditions: The apparatus composition of the electro-Fenton system is as follows Figure 1 As shown, the cathode is a modified carbon material cathode loaded with iron, and the anode is a ruthenium-iridium-titanium anode with a plate spacing of 50 mm. Air is pumped into the solution using an air pump under electric stirring at an aeration rate of 1.2 L / min. The solution contains 100 mg / L methyl orange, 50 mM Na₂SO₄, and a current density of 30 mA / cm². 2 After reacting at pH 3 and pH 7 for 240 min, the methyl orange content in the solution was measured, and the degradation rate was calculated. Both results showed a 99% degradation rate. Figure 8 As shown. Example 5
[0068] The preparation of iron-loaded modified carbon cathodes and the electro-Fenton method constructed thereon for removing chemical oxygen demand (COD) from the supernatant of secondary sedimentation tanks in urban wastewater treatment plants are described below:
[0069] (1) Preparation of modified carbon nanotube solid: 200 mg of carbon nanotube powder was placed in 70 wt% concentrated sulfuric acid, stirred, dried at 140 °C for 12 h, rinsed with deionized water until neutral, then ultrasonically treated in deionized water for 20 min, and then freeze-dried for 24 h to obtain modified carbon nanotube material.
[0070] (2) Preparation of iron-loaded modified carbon nanotube solid: Take 0.1g FeCl3·5H2O and put it into 20mL of anhydrous ethanol. Disperse 0.2g of modified carbon nanotubes into the solution and sonicate for 2h to make the solution into a paste. Then dry at 140℃ for 10h to obtain iron-loaded modified carbon nanotube solid.
[0071] (3) Preparation of iron-loaded modified carbon material cathode: The above-mentioned iron-loaded modified carbon nanotubes were placed in a mixed solution containing 1 mL of 60% wt polytetrafluoroethylene and 2 mL of analytical grade isopropanol. Then, 30 mL of pure water was added to the mixed solution. The mixed solution was evenly coated on 10 cm * 10 cm activated carbon fibers and ultrasonically treated for 15 min. Then, the carbon fiber cloth was turned over and ultrasonically treated for another 15 min. This process was repeated three times to ensure that the carbon material was fully attached to the activated carbon fibers. Then, the carbon nanotubes were dried at 90 °C for 24 h and then calcined in a muffle furnace at 360 °C for 2 h. After cooling, the iron-loaded modified carbon material was attached to a graphite plate to serve as a cathode.
[0072] (4) Electro-Fenton reaction conditions: The apparatus composition of the electro-Fenton system is as follows Figure 1 As shown, the cathode is a modified carbon material cathode loaded with iron, and the anode is a ruthenium-iridium-titanium anode with a plate spacing of 50 mm. Air is pumped into the solution using an air pump under electric stirring at an aeration rate of 1.2 L / min. The COD in the supernatant of the secondary sedimentation tank is 113.5 mg / L, with 50 mM Na₂SO₄, and the current density is 30 mA / cm². 2 After reacting at pH 7 for 240 min, the COD value was measured, and the calculated COD removal rate was 67.1%. Figure 9 As shown.
Claims
1. The application of an iron-loaded modified carbon material as a cathode in the electro-Fenton process for treating organic pollutants, characterized in that, The preparation method of the iron-loaded modified carbon material includes the following steps: 1) Take carbon nanotube powder, immerse it in concentrated sulfuric acid, dry it, rinse it with deionized water until neutral, sonicate it for 20-30 minutes, filter it and freeze dry it to obtain modified carbon nanotubes with good dispersibility. 2) Dissolve iron salt in anhydrous ethanol, add the modified carbon nanotubes obtained in step 1), and sonicate for 100-200 min to disperse and load iron onto the carbon nanotubes. After drying, iron-loaded modified carbon nanotubes are obtained; wherein the iron content in the iron-loaded modified carbon nanotubes is 9%~20% by mass. 3) Grind the iron-loaded modified carbon nanotubes obtained in step 2) into powder, mix them evenly with polytetrafluoroethylene concentrate, dissolve them in isopropanol, stir and add deionized water, coat the resulting mixture on the surface of activated carbon fiber, ultrasonically treat it, and then dry and calcine it to obtain the iron-loaded modified carbon material. The cathode of the electro-Fenton process is made by attaching the modified carbon material loaded with iron to the surface of a graphite plate; the anode is selected from either a ruthenium-iridium-titanium electrode or a platinum electrode; the pH range is 3-9; the aeration device is an air pump with an aeration rate of 0.4-0.8 L / min; and the current density is 15-90 mA / cm². 2 .
2. The application according to claim 1, characterized in that, In step 1), the particle size of the carbon nanotube powder is less than 180 mesh; the concentrated sulfuric acid is a sulfuric acid aqueous solution with a weight percentage of 70-90 wt%.
3. The application according to claim 1, characterized in that, In step 1), the drying temperature is 140±5℃ and the time is 12~15h; the freeze-drying temperature is not greater than -50℃ and the vacuum degree is less than 15Pa.
4. The application according to claim 1, characterized in that, In step 2), the iron salt is one of ferric chloride FeCl3, ferric sulfate Fe2(SO4)3, or ferric nitrate Fe(NO3)3.
5. The application according to claim 1, characterized in that, In step 2), the amount of anhydrous ethanol added is 30~60 mL / mmol Fe; the drying temperature is 140±5℃, and the time is 9~12 h.
6. The application according to claim 1, characterized in that, In step 3), the iron-loaded modified carbon nanotubes are ground into powder with a particle size of less than 180 mesh; the weight ratio of the polytetrafluoroethylene concentrate is 60 wt%; for every 1 g of iron-loaded modified carbon nanotubes, 2-5 mL of polytetrafluoroethylene concentrate is added, and the mixture is dissolved in 4-10 mL of analytical grade isopropanol and mixed thoroughly. Then, 150-200 mL of deionized water is added and stirred thoroughly, and the mixture is then coated onto a surface with an area of 450-600 cm². 2 After ultrasonic treatment of the surface of activated carbon fiber for 15-25 minutes, the surface is flipped over and ultrasonic treatment is continued. This process is repeated 2-3 times.
7. The application according to claim 1, characterized in that, The drying temperature in step 3) is 80~100℃, and the drying time is 12~24h; the calcination temperature is 350~400℃, and the calcination is carried out in a muffle furnace for 2~3h.
8. The application according to claim 1, characterized in that: The cathode can be reused multiple times after being rinsed with deionized water 2-3 times.
Citation Information
Patent Citations
Preparation method and application of active carbon fiber modified cathode for electro-Fenton technology
CN113307332A